2016
DOI: 10.1021/acs.jctc.6b00997
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Fluorescence Lineshape Theory for Polynomial Potentials

Abstract: The modeling of vibrations in optical spectra relies heavily on the simplifications brought about by using harmonic oscillators. However, realistic molecular systems can deviate substantially from this description. We develop two methods which show that the extension to arbitrarily shaped potential energy surfaces is not only straightforward, but also efficient. These methods are applied to an electronic two-level system with potential energy surfaces of polynomial form and used to study anharmonic features su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 70 publications
1
33
0
Order By: Relevance
“…47 For more realistic non-harmonic potential energy surfaces, higher order cumulants will contribute to the lineshape. 54,55 The cumulants can be expressed in terms of time-ordered integrals of increasing orders of quantum time-correlation functions C δU of the energy gap fluctuation operator δU . For the second and third order cumulant, we can write…”
Section: A Linear Absorption Spectra In the Cumulant Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…47 For more realistic non-harmonic potential energy surfaces, higher order cumulants will contribute to the lineshape. 54,55 The cumulants can be expressed in terms of time-ordered integrals of increasing orders of quantum time-correlation functions C δU of the energy gap fluctuation operator δU . For the second and third order cumulant, we can write…”
Section: A Linear Absorption Spectra In the Cumulant Approachmentioning
confidence: 99%
“…with analogous expressions for higher order quantum correlation functions. 54 The second order cumulant contribution g 2 (t) is commonly expressed in terms of the spectral density of system-bath coupling J (ω) by switching into Fourier space and evaluating the time-ordered integrals analytically: 47…”
Section: A Linear Absorption Spectra In the Cumulant Approachmentioning
confidence: 99%
“…Treatment of anharmonic behaviour has been tackled by stochastic environments 29,30 , molecular dynamics simulations [31][32][33] , and by including anharmonicity in the system potential [34][35][36] . In this study we use anharmonic system potentials whilst also including an interacting environment via a) cmlds@leeds.ac.uk b) A.G.Dijkstra@leeds.ac.uk the stochastic Schrödinger equation 22,37,38 .…”
Section: Introductionmentioning
confidence: 99%
“…Anharmonicity and its effects can manifest itself in numerous ways. The shape of the entire potential can be important, as in the case of the Morse potential and generally in the case of polynomial potentials 34 . Additionally, displaced harmonic oscillators that have different curvatures are accredited with giving rise to non-standard spectral features 35,47 .…”
Section: Introductionmentioning
confidence: 99%
“…54 Furthermore, the log-normal distributions are quite common in nature. 55,56 From a theoretical point of view, different models have been constructed to account for the non-Gaussian effect 12,29,[57][58][59][60][61] and to investigate the spectral line shape of the time evolution of 2DCS. However, so far no systematic study of the effect of dynamics on the 2DCS has been reported for cases where the underlying frequency distribution is skewed.…”
Section: Introductionmentioning
confidence: 99%